2019
DOI: 10.1021/acsearthspacechem.9b00051
|View full text |Cite
|
Sign up to set email alerts
|

Zero- and High-Pressure Mechanisms in the Complex Forming Reactions of OH with Methanol and Formaldehyde at Low Temperatures

Abstract: A recent Ring Polymer Molecular Dynamics study of the reactions of OH with methanol and formaldehyde, at zero pressure and below 100 K, has shown the formation of long lived complexes, with long lifetimes, longer than 100 ns for the lower temperatures studied, 20-100 K (del Mazo-Sevillano et al., 2019). These long lifetimes support the existence of multi collision events with the He buffer-gas atoms under experimental conditions, as suggested by several transition state theory studies of these reactions. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…58 Work to analyze the pressure effect with the buffer gas, He, is being done. 78 The challenge is to calculate the tunneling rate constant, k tunnel (T ), and the redissociation rate, k rediss (T ), under similar conditions, since they involve different processes and degrees of freedom. TST methods do not properly take into account the nature of these long lived resonances and more adapted multidimensional quantum method must be designed for this purpose.…”
Section: T ≤ 200 Kmentioning
confidence: 99%
“…58 Work to analyze the pressure effect with the buffer gas, He, is being done. 78 The challenge is to calculate the tunneling rate constant, k tunnel (T ), and the redissociation rate, k rediss (T ), under similar conditions, since they involve different processes and degrees of freedom. TST methods do not properly take into account the nature of these long lived resonances and more adapted multidimensional quantum method must be designed for this purpose.…”
Section: T ≤ 200 Kmentioning
confidence: 99%
“…What is different in RPMD calculations, is that there is an increasing probability of trapped trajectories as temperature decreases below 300 K. Those trapped trajectories are formed following an orbit similar to the QCT orbit of Fig. 9 as those shown in previous RPMD calculations in this system 29,30 : the long range interaction deviates the initial trajectories for rather long impact parameters, increasing the end-over-end angular momentum and the rotation of each of the two reactants. These trajectories get then trapped orbiting continuously keeping the relative orientation of the two reac-tants fixed, close to the geometry of reactant well, RC1.…”
Section: B Rpmd Resultsmentioning
confidence: 68%
“…The free polymer propagation was done using a Fourier transform (FT) 81 , and, being nearly exact, allows a large time step. In the previous RPMD calculations 29,30 it was also found that, for temperatures below 100 K, many trajectories were trapped in the complex well in the reactants channel. Those trapped trajectories lived for more than 500 ns, and were too long to be finished.…”
Section: B Rpmd Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This is effectively what is done in RPMD rate theory [29,30,41], where the t > 0 RPMD dynamics serves as an artificial, quantum-Boltzmann-conserving, classical dynamics, which gives a lower bound estimate of the t → 0 + flux through the optimal dividing surface [41,[78][79][80][81]. 9 For this reason, RPMD rate calculations give good approximations to the quantum rate coefficients for direct reactions [10,29,30,38,39,[82][83][84][85][86][87][88] and also for 'capture' reactions [89][90][91][92] involving statistically decoupled direct (capture and release) steps.…”
Section: Ring-polymer Molecular Dynamicsmentioning
confidence: 99%